Naḥwa Muqtaraḥ Tajdīdī fī Ta‘līm al-I‘rāb li-al-Nāṭiqīn bi-Ghayr al-‘Arabīyah - Mohamed el-Sayed Mohamed; EL-Sayed Mohamed Salem (Al-Ma‘rifah, 2019)
There were many complaints about the difficulty of grammar, both old and new, especially among learners of non-Arabic native speakers. Thus, it should be facilitated as a legitimate requirement and based on an educational basis. It is required only if things are difficult. Hence, it was necessary to propose a enhanced model for the inherited declension (i‘rāb), which is able to be expanded later for application in classrooms. There is no doubt that there is no magical way or secret idea for the students, which leads them directly to the desired goal, which is the composition ability of their sound pronunciation, and evaluate their tongues on the sound, but access to that valuable result is a combination of many factors enumerated research in the next pages. The research presented descriptive analytical, ends with exercises on what was proposed. The goal is clear, and the way to it is in the content (selection - arrangement - gradient), and then comes the good training based on the grounds of combining comprehensiveness and ease. If this is achieved, research has become important in that it is a cycle of facilitation, and an idea of ​​the development ideas sought by the institutions concerned with educational curricula and development.